Hydrogen storage properties and cycling degradation of single-phase La0.60R0.15Mg0·25Ni3.45 alloys with A2B7-type superlattice structure. (1st February 2020) - Liu, Jingjing; Cheng, Honghui; Han, Shumin; Liu, Hongfei; Huot, Jacques
Abstract: Single-phase La–Mg–Ni-based alloys show promising hydrogen storage performance. In this paper, we report the gaseous hydrogen storage characteristics, especially cycling performance of a series of A2 B7 -type single-phase La0.60 R0.15 Mg0·25 Ni3.45 ( R = Pr, Nd and Gd) alloys. These alloys are composed of [AB5 ] and [A2 B4 ] subunits stacking along c-axis in the ratio of 2:1. With cycling, degradation occurs which results in a sloped and increased plateau pressure, larger hysteresis and decreased hydrogen storage capacity. Structurally, the degradation is caused by the alloys' lattice expansion/contraction which leads to significant microstrain and decrease in grain size. It is found that the alloy with R = Gd experiences minimal microstrain and preserves good crystallinity during hydrogen absorption/desorption owing to its almost equal [A2 B4 ] and [AB5 ] subunit volumes. The R = Gd alloy achieved a cycling retention of 89.5% after 100 cycles compared with 79.8%–81.8% for the other two alloys. Additionally, the R = Gd alloy also possesses high reversibility, flat plateau and small hysteresis, showing a great potential in the hydrogen storage applications. Highlights: Single-phase La0.60 R0.15 Mg0·25 Ni3.45 superlattice alloys were successfully prepared. Gd is firstly found to make V [A2B4] and V [AB5] more equal which lowers microstrain. R = Gd alloy preserves good crystallinity after 100H2 absorption/desorption cycles. S 100 of R = Gd alloy is significantly improved compared with R = Pr and Nd alloys.